Middle Construction Acquisition in Spanish as a Second Language - Guillén Solano, Patricia (2016)
This article studies the acquisition of the middle voice in Spanish as a second language, focusing on the use of the pronoun se as a strategy for expressing anticausativity. The research is conducted on six Spanish as a second language speakers. Three of them have learned Spanish in a formal setting at university level and the other three have not, but they have lived in Costa Rica for a period of at least three years. In order to do the study, participants are required to answer the question ¿Qué le pasó a..? according to a series of pictures, in order to determine the use of the studied structure. Finally, their answers are analyzed and compared.